Transform Customer Experience : How to achieve customer success and create exceptional CX - Villani, Isabella (John Wiley and Sons, Inc. : Wiley, 2019)
Your customers are your future. Smartphones, social media and the internet have given customers access to more information than ever before. If your business fails them, they will switch to your competitor and never return. So how do you keep them' By mapping their journeys, identifying potential hazards and reshaping your business with customer experience (CX) at its heart.' From services to products, online to in-person, small-scale to multinational, your customers' loyalty depends on how you interact with them. Transform Customer Experience is your ultimate guide to putting your customer first. Author and CX expert Isabella Villani shows how you can implement a customer strategy from planning to execution.' Transform Customer Experience offers real-life insights into effective strategies for developing and implementing Customer Experience (CX) programs in a range of corporate, governmental and non-profit environments.-'Shows you how to address dimensions of diversity in the customer base -'Outlines customer journey mapping -'Discusses the implications of customers' omnichannel engagement -'Addresses the importance of positive employee experience in establishing a supportive CX culture. Transform Customer Experience explains why you need to embed customer experience in your organisation and shows you how to do it.'